Pre-frontal Cortex Oxygenation Changes During Aerobic Exercise in Elite Athletes Experiencing Sport-Related Concussion - Neary, J. Patrick; Dudé, Carolynn M.; Singh, Jyotpal; Len, Trevor K.; Bhambhani, Yagesh N. (Frontiers in Human Neuroscience, 2020)
Aims: Recent research suggests that aerobic exercise can be performed safely within the first week following concussion injury, and that early initiation of exercise may speed recovery. To better understand the physiological changes during concussion, we tested the hypothesis that mild-to-intense exercise testing can be performed within days immediately following injury, and can be used to discern differences between the concussed and normal healthy state. Thus, the purpose was to observe the cerebral haemodynamic responses to incremental exercise testing performed acutely post-concussion in high performance athletes. Methods: This study was a within- and between-experimental design, with seven male university ice hockey teams participating. A subgroup of 5 players acted as control subjects (CON) and were tested at the same time as the 14 concussed (mTBI) players on Day 2, 4, and 7 post-concussion. A five-minute resting baseline, and five-minute exercise bouts of mild (EX1), moderate (EX2), and high (EX3) intensity exercise was performed on a cycle ergometer. Near infrared spectroscopy was used to monitor pre-frontal cortex oxy-haemoglobin (HbO2), deoxy-haemoglobin (HHb), and total blood volume (tHb) changes. Results: ANOVA compared differences between testing days and groups, and although large percentage changes in HbO2 (20-30%), HHb (30-40%), and tHb (30-40%) were recorded, no significant (p≤0.05) differences in cerebral haemodynamics occurred between mTBI vs. CON during aerobic exercise testing on any day post-injury. Furthermore, there was a linear relationship between exercise intensity vs. cerebral haemodynamics during testing for each day (r2=0.83-0.99). Conclusion: These results demonstrate two novel findings: 1) mild-to-intense aerobic exercise testing can be performed safely as early as Day 2 post-concussion injury in a controlled laboratory environment, and 2) evidence-based objective measures such as cerebral hemodynamics can easily be collected using NIRS to monitor physiological changes during the first week post-injury. This research has important implications for monitoring physiological recovery post-injury, and establishing new rehabilitation guidelines.